FORMULASI SEDIAAN EMULGEL ANTIBAKTERI EKSTRAK BIJI KOPI ROBUSTA (Coffea canephora L.) SEBAGAI PENYEMBUHAN LUKA DIABETES - Novitaria Br Sembiring; Nerly Juli Pranita Simanjuntak; Ely Rosaulina Br Purba (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
Diabetic wounds are one of the complications of diabetes mellitus and are often accompanied by bacterial infection, which may delay the healing process. The use of natural ingredients as topical antibacterial agents is considered a potential alternative. Robusta coffee beans (Coffea canephora L.) are known to contain bioactive compounds with potential antibacterial activity. This study aimed to formulate Robusta coffee bean extract into an emulgel dosage form and evaluate its antibacterial activity against Staphylococcus epidermidis. This research was an experimental laboratory study. Extraction was carried out using the maceration method with 70% ethanol as the solvent. The emulgel was formulated in three extract concentrations, namely 20%, 30%, and 50%, and its antibacterial activity was evaluated using the well diffusion method, with clindamycin gel as the positive control and emulgel base as the negative control. The results showed that Robusta coffee bean extract contained flavonoids, alkaloids, and tannins. The antibacterial activity test of the extract showed inhibition zone diameters ranging from 15.09 to 18.21 mm, while the emulgel preparation produced mean inhibition zone diameters of 8.03 ± 0.73 mm at 20%, 10.08 ± 0.34 mm at 30%, and 13.08 ± 0.11 mm at 50%. The 50% emulgel formula showed the best antibacterial activity, although it was still lower than the positive control. Based on these findings, Robusta coffee bean extract has the potential to be developed as a natural active ingredient in topical antibacterial emulgel preparations.